The Impact of Financial Literacy and Recovery Strategy on Recovery Rate Among Customers of PT Bank Rakyat Indonesia (Persero) Tbk in Bandung City - Untoro Widagdo; Popy Rufaidah (Jurnal Aplikasi Bisnis dan Manajemen, 2026)
Background: Credit recovery among micro and small enterprises remains a significant challenge in developing economies, where non-performing loans (NPLs) are prevalent. Traditional approaches to credit recovery often emphasize institutional metrics such as repayment rates and financial ratios. However, recent developments highlight the importance of behavioral and perceptual factors, including borrower trust, fairness perception, and financial literacy. These psychological dimensions influence how borrowers respond to recovery strategies, particularly in the context of microfinance, where personal interaction and borrower experience are crucial.Purpose: This study aims to analyze the influence of financial literacy and recovery strategies on the perceived recovery rate among borrowers who have experienced default. It further explores how behavioral and perceptual factors contribute to credit recovery dynamics, moving beyond purely financial measures.Design/methodology/approach: The study employs a quantitative research design using Partial Least Squares Structural Equation Modeling (PLS-SEM) to test the proposed model. Data was collected through structured questionnaires from 240 micro and small enterprise borrowers at BRI Bandung with non-performing loans. The main variables examined are financial literacy, recovery strategy, and recovery rate, with an emphasis on perceptual and behavioral dimensions.Findings/Result: The results show that financial literacy significantly and positively affects the recovery rate. Additionally, recovery strategies, reflecting borrowers’ experiences with the bank’s recovery efforts, also significantly influence their perception of recovery outcomes. The findings suggest that psychological and perceptual factors, as explained by the Theory of Planned Behavior, are as important as financial metrics in determining credit recovery performance.Conclusion: The study concludes that financial institutions should not rely solely on enforcing repayment through traditional mechanisms but must also emphasize borrower-centered recovery strategies. Enhancing financial literacy, trust, understanding, and perceived fairness can improve loan recovery outcomes and contribute to sustainable credit rehabilitation in microfinance contexts.Originality/value (State of the art): This research introduces a novel framework by integrating perceived recovery as a key perceptual variable in management studies. By applying psychometric concepts to credit recovery evaluation, the study shifts the analytical focus from institutional performance indicators toward borrower experiences and trust. This contribution highlights the behavioral and perceptual dimensions of credit recovery, offering new insights into microfinance management and financial education strategies. Keywords:  financial literacy, perceived recovery strategy, perceived recovery rate, credit recovery, non-performing loans